Experimental and numerical assessment of global and local stability of steel-UHPC composite alveolar beams under hogging bending - Oliveira, Vinicius Moura de (2025)
Continuous steel-concrete composite beams provide bending moment redistribution, slight deflection, the capability to cover longer spans, and cost-effectiveness. Employing steel alveolar I-sections, High-Strength Steel (HSS), and Ultra-High-Performance Concrete (UHPC) slabs in these composite beams can significantly dematerialize the structure. To the best of authors' knowledge, no studies have addressed the adoption of high-performance materials for composite alveolar beams. At the same time, composite alveolar beams under hogging bending with shear forces can reach local and global instability or the interaction between the modes, such as Lateral-Distortional Buckling (LDB) and Web-Post Buckling (WPB), requiring further investigation. The present study aimed to investigate the occurrence of LDB and WPB in composite alveolar beams, considering HSS I-sections and UHPC. For these objectives, both experimental and numerical analyses were conducted. Three-point bending tests were carried out in steel-UHPC composite castellated beams with I-sections of microalloyed steels with Niobium addition. The experimental results were used to validate the numerical model, and numerical parametric studies were also conducted. The specimens reached failure by WPB coupled with the Vierendeel mechanism (VM). This way, the length of the web openings' hexagon horizontal edge (tee length) influenced the bearing capacity of the castellated beam, in which the specimen with a higher tee length had a lower ultimate load, which was also observed in the numerical parametric study. In addition, the numerical models with the shortest web-post width were more critical for the WPB occurrence. The parametric study models also reached failure by LDB coupled with WPB, showing an elevated influence of the I-section steel yield strength, and composite castellated beams with UHPC slabs showed higher initial bending stiffness and ultimate loads than those with Normal Concrete (NC) slabs. Given this, some possibilities to dematerialize conventional composite beams under hogging bending by using HSS castellated I-sections and slabs of UHPC were verified. The dematerialization rate considered in the analysis regards the ratio between the volume of material consumption of the conventional element and the dematerialized element. Even when instability modes occur in the I-section, an I-section dematerialization rate of up to 55% can be reached using HSS castellated I-sections. In addition, only adopting the castellated I-sections, without changing the steel yield strength, can present an I-section dematerialization rate of up to 17.9%. The slab concrete can reach the dematerialization rate of 33.3% by utilizing UHPC instead of NC. Finally, the updates in ABNT NBR 8800:2024 presented a more accurate LDB resistance prediction than the previous version (ABNT NBR 8800:2008). In most cases, European codes (EC4/EC3) provided conservative LDB and WPB resistance prediction.